Odpowiedzi

2010-03-29T23:33:15+02:00
X+y = 3
1/3x-1/3y-1/2x-1/2y = -1/2 |*6

x = 3-y
2x-2y-3x-3y = -3

x = 3-y
-x-5y = -3

x = 3-y
-(3-y)-5y = -3

x = 3-y
-3+y-5y = -3

x = 3-y
-4y = 0 |:(-4)

x = 3-y
y = 0

x = 3-0 = 3
2010-03-29T23:35:27+02:00
⅓x-⅓y-½x-½y=-½/×6
x+y=3

2x-2y-3x-3y=-3
x=3-y

-x-5y=-3
-(3-y)-5y=-3
-3+y-5y=-3
-4y=-3+3
-4y=0
y=0
x=3-0=0

x=3
y=0
Najlepsza Odpowiedź!
2010-03-30T00:36:14+02:00
1/3 x - 1/3 y - 1/2 x - 1/2 y =-1/2 /*6
x+y=3

2x-2y-3x-3y=-3
y=3-x

-x-5y=-3
y=3-x

-x-5(3-x)=-3
y=3-x

-x-15+5x=-3
y=3-x

4x-15=-3
y=3-x

4x=12
y=3-x

x=3
y=3-3

x=3
y=0